Effect of EPS Geofoam on Deformation and Stress Distribution in Shallow Buried Flexible Pipes - Gulen, Murat; Kilic, Havvanur (SPRINGER INDIA, 2026)
For several decades, the use of high compressibility materials has been proposed and applied in practice to reduce the stresses and deformations on structures by exploiting the arching effect in a variety of engineering applications. In this study, the use of Expanded Polystyrene (EPS Geofoam) at different densities to reduce the stresses and pipe section deflections exerted on a shallow buried 315 mm diameter high-density polyethylene pipe under strip loading conditions was investigated by full-scale laboratory tests. These test results were verified using two-dimensional numerical analyses. In addition, parametric studies were carried out to investigate various factors including burial depth, pipe and backfill properties, different EPS Geofoam dimensions and pavement stiffness. The vertical deformation of the pipe and EPS Geofoam, the deformation shape of the pipe and the arching effect result in significant modifications of the horizontal and vertical stress ratio in the soil surrounding the pipe. In the final case, the change in stress ratio and the arching effect reduced the stresses acting on the pipe by 40%, while reducing the deflections of the pipe by 32%. The results of the full-scale laboratory tests and numerical analyses demonstrate the applicability of EPS Geofoam in shallowly buried flexible pipe systems at stress levels where it behaves elastically.
Keywords: Arcing; EPS Geofoam; Stress redistribution; Stress ratio; Flexible pipe; HIGH-DENSITY POLYETHYLENE; FIELD PERFORMANCE; MODEL; CULVERT; Engineering